Trait structure reveals the processes underlying fish establishment in the Mediterranean. Issue 2 (30th September 2016) - Givan, Or; Parravicini, Valeriano; Kulbicki, Michel; Belmaker, Jonathan
Abstract: Aim: Typically, non‐indigenous species have been studied in relation to either the invaded (recipient) community or the donor community. However, we still lack a broad understanding of the mechanisms underlying the establishment of non‐indigenous species that combines both perspectives. Since the opening of the Suez Canal, hundreds of species have invaded the Mediterranean from the Red Sea, forming a unique system in which the entire species pool (donor, non‐indigenous and recipient) is known. Focusing on species ecological traits, we assess the drivers underlying the establishment of non‐indigenous species from the onset of the invasion to the present. Location: The Mediterranean and Red Seas. Methods: We compiled traits for shallow‐water hard‐bottom‐associated fishes in the Mediterranean (recipient community) and the Red Sea (donor community). We compared the multivariate community trait structure of non‐indigenous species with the donor and recipient assemblages, using a novel method to objectively assign trait‐weights, thereby increasing the robustness of the results. Patterns were contrasted with two types of null models which provide distinct insights into the ecological processes. Results: Non‐indigenous fishes are very diverse ecologically, substantially increasing the total community trait diversity of the Mediterranean. Trait similarity between non‐indigenous and indigenous Mediterranean species was lower than expected, indicating that non‐indigenous fishes tend to occupy relatively vacant niches within the Mediterranean. However, we further found that over time non‐indigenous species display increased trait similarity to indigenous Mediterranean species. This suggests that trait constraints associated with successful establishment are weakening. Main conclusions: Non‐indigenous species establish in relatively vacant ecological niches, opening the possibility for predicting establishment using ecological traits. However, the weakening of trait constraints through time suggests that forecasting future establishment may be difficult. Faced with an accelerating pace of invasion, it appears that the Mediterranean is going to be transformed into an extension of the Red Sea in terms of trait and species composition.